IN MEMORY OF PIERA SPADEA - Roda, Cesare (Ofioliti, 2024)
Piera graduated ‘Magna cum Laude’ at the University of Padua in 1961, discussing a thesis on field mapping and petrography of the Garian vulcanites, Libia. After a year in Padua with a scholarship she moved to Milan where she did research on the Karakorum Chain, Pakistan, collaborating with prof. Ardito Desio, and on the Triassic volcanoclastic rocks of Friuli, together with Prof. Riccardo Assereto. We met in 1963, in a beautiful spring day on the Etna Volcano, and since then our life journeys became entwined. In 1966 we got married and Piera moved to Catania, where I then lived.Following the suggestion of Prof. Leo Ogniben, who very much appreciated the studies that were performed in those years on Ophiolites by the young research group of the University of Florence, Piera began to do research on Ophiolites, that she continued until few weeks before her death. This line of research brought Piera to study rocks of various Italian regions: Lucania, Calabria, Liguria, often in cooperation with her colleagues from Florence, and other ophiolitic areas, like Corsica, the Northern Andes in Colombia, the Urals, where she established collaboration projects with many scientists worldwide. I here just mention among them, Prof. Marc Vuagnat, one of the pioneers in ophiolite studies, that had a great influence on Piera, and Prof. Adolphe Nicolas, whose studies on the relationships between ophiolites and present oceanic rocks have been for Piera an important reference point.From ophiolites she quickly jumped to do research on modern oceanic crustal rocks; she first participated in 1989 to the international Ocean Drilling Project in Sulu and Celebes, Pacific Ocean. She continued in 1991 with a dredging campaign in the Tyrrhenian Sea on the Russian ship Antares, and the last one was in 1993 when she participated to the exploration of fastspreading Mid oceanic Ridges on the submersible Nautile of the Ifremer, where she reached 5,000 meters below sea level.The results from these researches highlighted her as a scientist, inasmuch as to Piera being called to be part of the research projects evaluation committee for ODP (Joides Sterring and Valuation Panel on the Dynamics of Earth Interior). In this role she organized in year 2000 in Udine the Committee Meeting, where scientists from all over the world attended: Piera was the only Italian one. The meeting coincided with an exhacerbation of her illness, so that it could be held just thanks to her colleagues from OGS.Love for rocks also brought Piera to study them as building materials, in particular the stones used in art pieces and their degradation and weathering processes; in this field too, that Piera considered her ‘weekend’ job, she achieved significant results.Up until a few weeks before her demise, Piera continued to work and communicate with her colleagues for researches that were in press, in particular for the present Issue of ‘Ofioliti’, for refereeing geology papers from her colleagues and for organizing new research projects.Then, on August 13, Piera left us and many threads were cut.What remains are the words of affection and esteem of many of her colleagues and the memory of her enthusiasm.